The Design of Calibration System Based on Cable Accessories. Issue 1 (1st February 2023) - Zhao, Tiemin; Liu, Jianshu; Zheng, Shiyang; LeYang,; Ding, Zhen; Li, Dongsheng; Li, Kai; Li, Wenpeng; Yang, Xue; Chai, Fangsen
Abstract: In today's society, people can't live without electricity. During the operation of power equipment, there may be various potential safety risks. In particular, partial discharge is easy to occur at the terminal. If people can not deal with the problem of partial discharge in time, equipment continue to live.Setting can cause security, so the electric power industry staff attaches great importance to the local discharge monitoring problem.Ultrasonic technology is better so it is gradually into the application of partial discharge detection.But the ultrasonic detection technology is to detect the intensity of ultrasound, and our traditional method is to measure the discharge of partial discharge method, Therefore, in order to obtain the relationship between ultrasonic intensity and partial discharge, the following experiments are made. After we pass the power frequency voltage withstand device, the transformer is continuously pressurized.Gain DB and discharge PC were obtained by digital partial discharge instrument and ultrasonic partial discharge instrument. After fitting, the linear relation is obtained and the quality inspection of PD detector is completed.It can make the detection effect of partial discharge detector more complete, and provide the basis for the quality inspection of the detector, This system also provides a strong support for the wide application of ultrasonic partial discharge detector.